Changes in plasma circulating microvesicles in patients with HCV‐related cirrhosis after treatment with direct‐acting antivirals. (10th September 2019) - Campello, Elena; Radu, Claudia M.; Zanetto, Alberto; Bulato, Cristiana; Shalaby, Sarah; Spiezia, Luca; Franceschet, Enrica; Burra, Patrizia; Russo, Francesco P.; Simioni, Paolo
Abstract: Background & Aims: The eradication of Hepatitis C (HCV) infection by direct‐acting antiviral (DAAs) agents has been linked to an amelioration of liver synthesis and regression of fibrosis. Although changes in number and type of circulating microvesicles (MVs) have been reported in cirrhosis, conclusive data on the effect of DAAs treatment on MVs profile in HCV cirrhotic patients remain scarce. Methods: We measured the levels of endothelial, platelet and hepatocyte MVs, as well as MVs‐expressing versican core protein (VCAN+) in patients with HCV‐related cirrhosis at baseline, end of treatment (EOT), at 12, 24 and 48 weeks (W) after EOT by new generation flow cytometry. Results: Fifty‐eight patients were enrolled (86% Child's A). MVs were increased at EOT vs baseline, though only platelet MVs revealed a statistically significant difference ( P  < .01). MV levels did not change significantly after EOT notwithstanding a steady downward trend towards baseline levels. Conversely, VCAN + MVs dropped significantly at EOT ( P  < .001) and remained low throughout the follow‐up. Hepatocyte MVs significantly correlated with liver stiffness (r = .40, P  = .0021). Eight composite outcomes occurred during the 1‐year follow‐up: three portal vein thromboses (PVTs), two hepatocellular carcinomas (HCCs) and three liver decompensation. Child's B, the presence of F2 oesophageal varices (OR for interaction 19.2 [95% CI 1.45‐253.7], P  = .023) and platelet MVs (OR 1.026 [95% CI 1.00‐1.05, P  = .023) correlated significantly with clinical outcomes. Conclusions: VCAN + MVs appear to mirror the profibrotic status of the cirrhotic disease; hepatocyte MVs correlate with liver stiffness and increased platelet MV levels could be associated with a worse clinical outcome.